Analisis Kesulitan Belajar Matematika Siswa Kelas II Sekolah Dasar pada Materi Waktu - Fitri, Dea My (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
Mathematics learning is widely seen as a difficult subject to learn. Due to the need for  efforts that must be made to understand the material. Especially at the elementary school level,  where this level is the main milestone in the next learning process. One of them is grade II  elementary school students in learning math on time material. This study aims to analyze the  difficulties experienced by students during the mathematics learning process in mathematics on  the material of time. The research used is qualitative research with descriptive methods. In the  process of collecting data using a questionnaire with a Likert scale. The study population was  grade II elementary school students and the sample was grade II B students from the results of  the indicators set by the researcher. The average of each indicator is 63%, this means that the  learning difficulties experienced by students are in the high category. The questionnaire is made  by categorizing several indicators, namely motivation and interest in learning mathematics,  difficulties in understanding and the methods used by the teacher.